2023
DOI: 10.1590/0103-8478cr20210801
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of leg and ear numbers in radio frequency identification systems (RFID) in sensitive livestock products in goat breeding

Abstract: This study, evaluated the readability of electronic leg and ear tags in Saanen goats. Fifty-seven goats were identified with the electronic leg tags (ELT) and electronic ear tags (EET) from birth until the lactation period ends. Readability of ELT and EET was 96.30% and 90.55% respectively in static conditions at the end of 12 months. Foot and udder, with no infection rates for ELT and EET in calm and aggressive goats were 95.70% and 100%, respectively. No infection rates of foot and udder for ELT and EET in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been demonstrated by Garcia et al that the use of transponders is feasible for the EID of water buffaloes, and they recommended that electronic transponders be implanted in calves that are up to two months of age, as this reduces the physical rate of transponder loss and the loss of functionality [ 87 ]. Kandemir et al employed electronic leg tags (ELT) and electronic ear tags (EET) to identify goats and concluded that the traceability of ear-tagged animals was inferior [ 88 ]. Non-invasive biometric identification could greatly enhance animal welfare and management in livestock farming.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated by Garcia et al that the use of transponders is feasible for the EID of water buffaloes, and they recommended that electronic transponders be implanted in calves that are up to two months of age, as this reduces the physical rate of transponder loss and the loss of functionality [ 87 ]. Kandemir et al employed electronic leg tags (ELT) and electronic ear tags (EET) to identify goats and concluded that the traceability of ear-tagged animals was inferior [ 88 ]. Non-invasive biometric identification could greatly enhance animal welfare and management in livestock farming.…”
Section: Resultsmentioning
confidence: 99%